2021
DOI: 10.3389/fendo.2021.577919
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Antipsychotic-Induced Weight Gain: A Systematic Review and Meta-Analysis

Abstract: Background and AimsWeight gain is a major adverse effect of antipsychotic medication, negatively affecting physical and mental well-being. The objective of this study was to explore if dose reduction, discontinuation, switch to a partial agonist, or switch from polypharmacy to monotherapy will lead to weight loss.MethodsControlled and uncontrolled studies reporting the effects of discontinuation, dose reduction, switch to a partial agonist, or switch from polypharmacy to monotherapy on weight were included. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…However, for most assessments, average weight differences between higher and lower doses did not differ to a clinically significant extent, although studies were of short duration [59]. A separate review highlighting dose reduction as ineffective in significantly reversing AIWG supports the hypothesis of AIWG being somewhat dose-independent [60], although the absence of linear relationships may mean dose reductions are more effective within certain ranges. Taken together, additional research is required to confirm whether antipsychotic dosing meaningfully impacts AIWG prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, for most assessments, average weight differences between higher and lower doses did not differ to a clinically significant extent, although studies were of short duration [59]. A separate review highlighting dose reduction as ineffective in significantly reversing AIWG supports the hypothesis of AIWG being somewhat dose-independent [60], although the absence of linear relationships may mean dose reductions are more effective within certain ranges. Taken together, additional research is required to confirm whether antipsychotic dosing meaningfully impacts AIWG prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believe that OLZ treatment should be coupled with real-time monitoring and must be switched swiftly to other antipsychotics in case of intense adverse events. [6][7][8] Various perspectives propose co-administering metformin, topiramate, and reboxetine to reduce weight gain is also a viable option. 9,10 The new application of SAM appears to provide an additional therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Moreover, it is well known that long-term maintenance of weight loss following lifestyle interventions is challenging. 14,15 Depressive and negative symptoms may negatively impact the implementation of lifestyle interventions. Furthermore, participants of clinical trials are potentially better able to stay motivated and to follow structured lifestyle programs than patients in clinical practice depending on the severity of illness.…”
mentioning
confidence: 99%
“…However, studies demonstrated variable efficacy of lifestyle interventions 12,13 . Moreover, it is well known that long‐term maintenance of weight loss following lifestyle interventions is challenging 14,15 . Depressive and negative symptoms may negatively impact the implementation of lifestyle interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation